Perbandingan Kualitas Produk Sayur dan Buah pada Pasar Tradisional dan Pasar Modern di Kota Serang dalam Penerapan Strategi Pamasaran - Khaeruman Khaeruman; Hafidz Hanafiah (Majalah Ilmiah Bijak, 2019)
Agricultural products are types of products that have disadvantages, among others: perishable and short shelf life, especially for horticulture. These weaknesses cause horticultural products to require special treatment from pre-harvest to post-harvest so that the quality does not decrease. A decrease in product quality will affect its sale value in the market. However, special handling requires additional costs, so the amount of post-harvest handling must also consider the demand of the buyer.